Organic Nanoparticle Genotoxicity: Current Understanding and Future Testing Needs - Sadaqa, Ebrahim; Setiawansyah, Arif; Nugroho, Bambang Hernawan; Hidayati, Nurul; Arsul, Muhammad Ikhlas (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2024)
Organic nanoparticles derived from biocompatible materials like chitosan, alginate, and lipids have garnered immense interest for drug delivery, bioimaging, and other biomedical applications. However, as their use rapidly expands, a comprehensive evaluation of their potential genotoxicity is crucial to ensure safe implementation. This review provides an in-depth analysis of the genotoxic risks associated with these organic nanoparticles. The review elucidates how the unique physicochemical properties of organic nanoparticles can induce genetic damage through mechanisms such as direct DNA binding, oxidative stress, inflammation, and impairment of DNA repair pathways. Importantly, this genotoxicity can occur even in the absence of overt cytotoxicity, leading to heritable mutations and long-term adverse effects like cancer and reproductive abnormalities. A critical assessment of established and emerging genotoxicity testing methods, including their strengths, limitations, and opportunities for standardization, is presented. The review synthesizes findings from existing in vitro and in vivo studies, revealing the contrasting genotoxic profiles of different organic nanoparticle formulations and exposure scenarios. Furthermore, the review provides insights into the multifaceted factors influencing nanoparticle genotoxicity, guiding the strategic engineering of safer designs. This comprehensive analysis underscores the pivotal importance of rigorous genotoxicity screening in the responsible development of organic nanomaterials. By harmonizing their innovative capabilities with a commitment to genetic integrity, this review paves the way for realizing the vast potential of organic nanoparticles while safeguarding human and environmental health.